2021
DOI: 10.3390/app112311330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Some Graphene Oxide Powders Used as Additives in Hydraulic Mortars

Abstract: Various powders of graphene oxide (GO), GO with silver (GO-Ag) and zinc oxide (GO-ZnO) were obtained. The powders were silanized with (3-aminopropyl) triethoxysilane (APTES) aiming to be used, in a future stage, as additives in the hydraulic lime mortars composition. The powders were characterized by Fourier Transform Infrared Spectrometry (FTIR) and Scanning Electron Microscopy (SEM) before and after the silanization process. GO, GO-Ag, GO-Ag-APTES, GO-ZnO and GO-ZnO-APTES powders were also investigated by Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
(83 reference statements)
2
24
0
Order By: Relevance
“…The band at 1530 cm −1 pointed out the skeletal vibration of the graphene sheets 66 . The peak at 1360 cm −1 is assigned to O‐H deformations of the C‐OH 66 . The band at 1055 could refer to the alkoxy group vibrations 68 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band at 1530 cm −1 pointed out the skeletal vibration of the graphene sheets 66 . The peak at 1360 cm −1 is assigned to O‐H deformations of the C‐OH 66 . The band at 1055 could refer to the alkoxy group vibrations 68 .…”
Section: Resultsmentioning
confidence: 99%
“…The broad band at 3400 cm À1 is attributed to -OH (hydroxyl group) stretching vibration which arose from the vibration of hydroxyl groups, 65 indicating the hydrophilic feature of synthesized nanopowder, which was highly observed in prior reports. 66 The fine structure at 2930 is attributed to the C-H stretching vibration 67 from the alkane group. The band at 1530 cm À1 pointed out the skeletal vibration of the graphene sheets.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Several peculiarities deal with absorption bands at 1729 and 1619 cm −1 , which are distinctive features of any GO sample. There is some ambiguity in the interpretation of the band at 1619 cm −1 , which could be assigned to C=C [ 107 , 108 , 109 ]. However, this band corresponds to the absorption of water molecules embedded in graphite layers, proven by isotopic exchange with D 2 O [ 110 , 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…It could be attributed to the stretching vibrations of the hydroxyl group from Ca(OH) 2 . The wide band at 3436 cm −1 corresponds to the stretching vibrations of the O-H bond, which can also be attributed to the oxygen groups found both on the surface and at the edge of the GO sheets [8,33]. The third band could be assigned to the carbonatite phases, while the fourth one corresponds to the Si-O stretching vibrations.…”
Section: Fourier Transform Infrared Spectrometry (Ft-ir)mentioning
confidence: 96%
“…Recently, it was found that various nanomaterials, such as nano-TiO 2 [6,7] and graphene [8,9] could be successfully used to improve the mechanical properties and durability of the mortars [10][11][12]. Nano-TiO 2 has been also proved an excellent photocatalytic material that imparts biocidal, self-cleaning, and smog-abating functionalities when added to cement-based materials [13,14].…”
Section: Introductionmentioning
confidence: 99%